Role of Platelet C‐Type Lectin‐Like Receptor 2 in Promoting Lung Metastasis in Osteosarcoma. (1st June 2020) - Ichikawa, Jiro; Ando, Takashi; Kawasaki, Tomonori; Sasaki, Tomoyuki; Shirai, Toshiaki; Tsukiji, Nagaharu; Kimura, Yujiro; Aoki, Kaoru; Hayakawa, Keiko; Suzuki‐Inoue, Katsue; Saitoh, Masao; Haro, Hirotaka
ABSTRACT: The overall prognosis of patients with sarcoma‐based cancers has changed little in the last 20 years. There is an urgent need to investigate the metastatic potential of these tumors and to develop anti‐metastatic drugs. It is becoming increasingly clear that platelets play an important role in the establishment of metastasis of carcinoma cells and could be a useful therapeutic target for patients with carcinoma. However, little is known about the role of platelets in sarcoma progression. Here, we investigated how osteosarcoma progression relates to platelet function to explore the possibility of anti‐platelet therapy. We found that, similar to carcinoma cells, podoplanin (also known as Aggrus)‐positive osteosarcoma cells induce platelet aggregation and activation. Administration of anti–glycoprotein Ibα (GPIbα, also known as CD42b) antibody reduced the lung metastasis of osteosarcoma. The supernatant from platelets cocultured with osteosarcoma cells contained several growth factors and promoted proliferation, invasiveness, and sphere formation of osteosarcoma cells in vitro. In addition, the development of lung metastasis was highly dependent on direct interaction between osteosarcoma cells and platelets. To explore the therapeutic target, we focused on the interactions between podoplanin on osteosarcoma and C‐type lectin‐like receptor (CLEC)‐2 on platelets. The administration of a depleting antibody against CLEC‐2 efficiently suppressed osteosarcoma metastasis into the lung. We also analyzed clinical data from patient samples at primary and metastatic sites. Although GPIbα expression was similar between the two sites, there was a significant increase in podoplanin at the metastatic site compared to that in the primary site, and the level of podoplanin expression in the primary site correlated with patient prognosis. These findings suggest that blockade of interactions between platelets CLEC‐2 and osteosarcoma podoplanin represent the most promising therapeutic strategy for preventing the lung metastasis of osteosarcoma. © 2020 American Society for Bone and Mineral Research.